Analysis of Sharia Financial Behavior Towards the Welfare of Fishermen’s Households in Berandan Kab. Langkat - Azra Nurwansyah, Nurul JannahNurul Jannah, Waizul Qarni (Amkop Management Accounting Review (AMAR), 2025)
This study examines the effect of Islamic financial behavior on the welfare of fishing households in Berandan through a qualitative case study approach. The results show that 90% of fishermen have savings of less than Rp500,000 due to unstable income (Rp1-4 million/month) influenced by the season and fluctuations in fish prices, with 60% relying on high-interest loans during lean periods. Although 80% of respondents are not accustomed to structured financial record-keeping and 55% lack understanding of Islamic finance terminology, 70% expressed interest in profit-sharing systems after receiving explanations, while 85% remain consistent in paying zakat/alms as a form of spiritual resilience. These findings recommend three integrated solutions: (1) practical Islamic finance training based on concrete examples, (2) the establishment of a BMT specifically for fishermen with Islamic financing products, and (3) a sustainable mentoring program by religious leaders, which is expected to increase the financial capacity of fishermen’s households by 40-60% in two years while strengthening the principles of maqasid syariah in the economic life of coastal communities.